Mannauðsstefna Strætó bs. - Júlía Þorvaldsdóttir 1975- (2010)
This project is the work method used to design a human resource strategy for Strætó bs. as well as it‘s actual design. It is based on an actual methodology where parties from four Danish companies were openly interviewed. Focus groups were also used to review the design and work on the strategy itself. In addition, pre-existing data which managers at Strætó bs. had gathered in recent years was processed, that mainly being data regarding the strategy of Strætó bs. and a workplace analysis done by an MBA study group from the University of Iceland. This was considered necessary in order for the project‘s HR strategy to rhyme with the HR work already accomplished by Strætó. Lessons learned from the prementioned foreign companies which apply to Strætó bs. will be covered in detail. Suggestions and ideas from the highly experienced employees and managers at Strætó bs. will also be considered and developed further. The before mentioned suggestions, pre-existing data and comparison with the strategies of municipalities in ownership of Strætó bs. were the focus poins of producing this HR strategy described in this project. Verkefnið er verklag við hönnun mannauðsstefnu fyrir Strætó bs. og eiginleg hönnun hennar. Framkvæmd var vettvangsathugun hjá fyrirtækjum í Danmörku sem eru í sambærilegum rekstri og Strætó bs. Kannað var hvort yfirlýstar stefnur væru til staðar í tilteknum fyrirtækjum þar í landi og hvort þær væru iðkaðar og hvernig fyrirtækjunum færist úr hendi að halda þeim við lýði. Gagnaöflun var með fjölbreyttum hætti, verkefnið byggir á eigindlegri aðferðafræði þar sem tekin voru opin viðtöl við aðila hjá fjórum dönskum fyrirtækjum. Ásamt því að kallaðir voru til rýnihópar við hönnun og vinnu við mannauðsstefnuna sjálfa. Einnig var unnið úr fyrirliggjandi gögnum sem stjórnendur Strætó hafa aflað síðastliðin ár. Þar ber helst að nefna gögn er varða stefnumótun Strætó ásamt vinnustaðagreiningu sem unnin var af MBA námshópi við Háskóla Íslands. Þetta var talið nauðsynlegt við gerð verkefnisins svo mannauðsstefnan ...